The effect of a Kohlberg’s theory of moral development-based intervention on ethical reasoning in nurse interns at Shahrekord University of Medical Sciences - Matin Soltani; Shahram Etemadifar; Soleiman Kheiri (Journal of Multidisciplinary Care, 2022)
Background and aims: Nursing students represent one of the most important healthcare professionals in the health system that, along with acquiring knowledge and practical skills, should learn professional values and attitudes and nursing care ethics. The aim of this study is to investigate the effect of an intervention based on Kohlberg’s theory of moral development on the ethical reasoning of nurse interns. Methods: The present quasi-experimental study was conducted with participation of 72 nurse interns in the teaching Ayatollah Kashani and Hajar hospitals affiliated to Shahrekord University of Medical Sciences from 2019 to 2021. The nurse interns were first selected based on the inclusion criteria by census and then randomly assigned to two groups of 36 each, namely, intervention and control. In the intervention group, educational content was performed in four sessions of one and a half hours within one month. Data collection tools included a demographic characteristics checklist and Nursing Dilemma Test (NDT) which was administered at baseline and immediately and one month after the intervention to both groups. Data were analyzed by SPSS version 24 using descriptive and analytical tests such as paired t-test, independent t-test and Fisher’s exact test at a significance level of 0.05. Results: The mean (±standard deviation) score of ethical reasoning before the moral intervention were 39.16±5.74 in the control group and 39.22±1.09 in the intervention group, with no statistically significant difference by independent t test (P=0.831). The mean±standard deviation score of this variable immediately after the moral intervention was obtained 39.08±5.26 in the control group and 39.41±6.58 in the intervention group, with no statistically significant difference by independent t test (P=0.370). But the mean±standard deviation score of ethical reasoning one month after the moral intervention was 38.94±5.68 in the control group and 47.77±6.71 in the intervention group, with a statistically significant difference by independent t test (P=0.001). Conclusion: Given that most nursing students have a low level of ethical reasoning, it is necessary for nursing managers to pay more attention to the issue of professional ethics in educating students in this field. The results of the present study indicated the desirable impact of Kohlberg’s moral intervention on the ethical reasoning of nurse interns, so it is recommended to give serious attention to the use of Kohlberg’s theory of moral development -based interventions in the education of nursing students.